Pre- Weaning traits of brahman calves under a dual-purpose management system in the tropics - Landaeta Hernández, Antonio; Rae, Owen; Olson, Timothy; Ferrer, José; Barboza, Marianela; Archbald, Louis (Revista Científica de la Facultad de Ciencias Veterinarias)
The objective of this study was to analyze factors associated with pre-weaning growth traits (e.g., weight and linear body measurements) and neonatal weakness in graded Red (RB, n=86) and Grey Brahman (GB, n=33) calves. Observed parameters included birth weight (BW), weight at 210-d (W210), average daily gain from birth to 210-d (ADG), and multiple linear body measurements. At birth, males were heavier (31.6 Ó 0.9 kg 28.5 Ó 0.8 kg; P < 0.002) than females, differences due to sire (P < 0.001) were observed, and calves experiencing NW tended to be lighter than normal calves (29 Ó 1.1 vs 31.2 Ó 0.6 kg; P < 0.06). At 210-d, males were heavier than females (124.7 Ó 3.2 vs 111 Ó 3.4 kg; P < 0.007), cows in their second and fourth parities had the heaviest (P < 0.001) calves. Heavier W210 (122.5 Ó 3.4 vs 113 Ó 3.1kg; P < 0.01) and greater ADG (0.451 + 0.01 vs 0.388 + 0.01 kg/d; P < 0.001) were found in calves born during dry season compared to those born during rainy season. Calves from second and fourth parity dams had greatest (P < 0.01) ADG. Both at birth and 210-d., all linear body traits and body weight were highly correlated (P < 0.001). Calves experiencing NW had reduced W210 (113 Ó 4 vs 122 Ó 2.6 kg; P < 0.05) thorax circumference, hip height and dorsal length (P < 0.001) compared to normals. Occurrence of NW was greater in RB than GB (P < 0.005). Three sires were found to be associated with NW (P < 0.005).